Farrar Copper Spine House, elevations (south and east), sheet no. 4 - Mark Mills::::::::: (1966)
Includes note: 'Concrete shall be tinted to match surrounding granite outcroppings. Roof surfaces shall be covered with crushed granite rock to match surrounding granite outcroppings.'